Comunicación interna y su incidencia en la satisfacción de los socios y clientes de la "COAC. C.D.C. del cantón Bolívar Ltda." - Ormaza Ferrín, Jonathan Alfredo (2024)
The purpose of this curricular integration work was to evaluate internal communication in order to determine its impact on the satisfaction of the members and customers of the COAC Chamber of Commerce of the Bolívar Canton Ltda. The research adheres to a mixed approach, where qualitative and quantitative research were combined. In addition to the analytical-synthetic, inductive, deductive and Delphi methods. Techniques such as document review, survey, cause-effect diagram and the 5W+2H matrix were used. In addition to the coefficient of expertise, Kendall agreement and Cronbach's alpha, which provided reliability and validity to the assessment instrument. The investigation procedure consisted of three phases. A situational diagnosis was carried out that allowed the identification of communication problems that have an impact on the satisfaction of the institution's partners and customers, in the indicators of tangible elements, reliability, responsiveness, security and empathy. Then, the statistical correlation of the variables was carried out, determining the existence of critical knots in the interpersonal communication indicator, causing problems in the reliability (0.810) and security (0.813) indicators. Similarly, in the intrapersonal communication indicator, there are setbacks in the indicators tangible elements (.997), responsiveness (.999) and empathy (.996). Therefore, it is concluded and recommended the implementation of the improvement plan proposed in this research that allows the institution to solve the causes and sub-causes that generate the problem, strengthening its internal communication and satisfaction of members and customers, contributing to the effectiveness and efficiency of the service offered.